2018
DOI: 10.1186/s12888-018-1823-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychiatric disorders among students aged 6~ 16 years old in central Hunan, China

Abstract: BackgroundThough several epidemiological surveys of psychiatric disorders have been carried out in China, only a few of them are concerned about the prevalence of psychiatric disorders in central Hunan and reveal the distribution of common psychiatric disorders and their comorbidities.MethodsAchenbach’s Child Behavior Checklist (CBCL), the Mini International Neuropsychiatric Interview for Children and Adolescents (MINI-KID), and Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
(66 reference statements)
5
23
3
1
Order By: Relevance
“…The two groups were matched on age, gender, and IQ (see Table 1). However, and consistent with the literature (Remes et al., 2018; Shen et al., 2018), 15 of the adolescents with GAD presented with comorbid major depressive disorder. Clinical characterization was done through psychiatric interviews by licensed and board‐certified psychiatrists with the participants and their parents, to adhere closely to common clinical practice.…”
Section: Methodssupporting
confidence: 87%
“…The two groups were matched on age, gender, and IQ (see Table 1). However, and consistent with the literature (Remes et al., 2018; Shen et al., 2018), 15 of the adolescents with GAD presented with comorbid major depressive disorder. Clinical characterization was done through psychiatric interviews by licensed and board‐certified psychiatrists with the participants and their parents, to adhere closely to common clinical practice.…”
Section: Methodssupporting
confidence: 87%
“…We observed a prevalent rate of 5.2% of mental health disorder among the school age children, which is lower than the global estimate of 10-20% [6,7,28], and the prevalence of 14.3% reported for Sub-Saharan Africa [37]. The prevalence in this study is also lower than that reported in Western Nigeria (11.4%) [38], China (9.74%) [39], and Italy (8.2%) [40]. It is however higher than the 3.5% and 2.9% reported in Ethiopia [40] and in Spain [41] respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…Classes from each Grades were randomly selected from each school, depending on the size of the school. [36,37] The participants were recruited between January 1, 2014 and December 31, 2014.…”
Section: Methodsmentioning
confidence: 99%